2006
DOI: 10.1111/j.1365-2559.2006.02410.x
|View full text |Cite
|
Sign up to set email alerts
|

Different patterns of inflammation and prognosis in invasive carcinoma of the breast

Abstract: Moderate or marked diffuse inflammation in breast cancer is associated with a better prognosis, suggesting that the immune effects of the inflammation predominate over the protumour effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
62
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 37 publications
7
62
1
Order By: Relevance
“…10,14 This is, at least in part, likely to be linked to histological grade as there is strong correlation between histological grade and intensity of inflammation 10 and 95% of tumours in the present series were grade 3. The separation of inflammation into two groups (absent and mild vs moderate and marked) was based on previous studies.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…10,14 This is, at least in part, likely to be linked to histological grade as there is strong correlation between histological grade and intensity of inflammation 10 and 95% of tumours in the present series were grade 3. The separation of inflammation into two groups (absent and mild vs moderate and marked) was based on previous studies.…”
Section: Discussionmentioning
confidence: 83%
“…[11][12][13] Also, if the Ridolfi criteria are strictly applied then less than 1% of carcinomas are of this type. 14 In addition, medullary carcinomas also share histological and immunophenotypic features with tumours that arise in carriers of BRCA1 germ-line mutations, which have a poor prognosis. 15 This study aimed to test the hypotheses that medullary histological features are associated with each other and with a better prognosis in invasive basal-like carcinomas.…”
mentioning
confidence: 99%
“…Lymphocytic infiltrate is known to be associated with good prognosis (Lee et al, 2006), and a recent study by Kreike et al (2007) focused on triple-negative sporadic breast tumours revealed that 5-year metastasis-free survival in patients with a moderate or large amount of lymphocytic infiltrate in their tumours was 88%, which was higher than for those with minimal or no lymphocytic infiltrate. In our case it was not possible to determine whether the signature could predict patient outcome independently of infiltrate status, due to the almost perfect correlation between the presence of infiltrate and absence of angioinvasion, but the same results in an independent series support the biological significance of the immune response in the classification of ER-negative BRCA1 tumours.…”
Section: Signatures Associated With Brca1 Tumoursmentioning
confidence: 99%
“…The presence of inflammatory cells may represent an immune response to the tumour, but could also potentially exhibit pro-tumour effects including stimulation of tumour invasion or angiogenesis. Some studies have reported that a dense lymphohistiocytic infiltrate is associated with a favourable prognosis [3,4], however, other reports have shown an association between prominent inflammation and a poor patient outcome [5]. A detailed understanding of the functional peculiarities and phenotype of individual T lymphocyte subtypes may explain this paradox [6].…”
Section: Introductionmentioning
confidence: 99%